2009
DOI: 10.5194/acpd-9-10055-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detailed heterogeneous chemistry in an urban plume box model: reversible co-adsorption of O<sub>3</sub>, NO<sub>2</sub>, and H<sub>2</sub>O on soot coated with benzo[a]pyrene

Abstract: Abstract. This study assesses in detail the effects of heterogeneous chemistry on the particle surface and gas-phase composition by modeling the reversible co-adsorption of O3, NO2, and H2O on soot coated with benzo[a]pyrene (BaP) for an urban plume scenario over a period of five days. By coupling the Pöschl-Rudich-Ammann (PRA) kinetic framework for aerosols (Pöschl et al., 2007) to a box model version of the gas phase mechanism RADM2, we are able to track individual concentrations of gas-phase and surface spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…At RH > 15 %, MNC is less reactive with OH, exhibiting γ < 0.07 due to competitive co-adsorption of water and OH (Slade and Knopf, 2014). Similar suppressions in gas uptake, due to competitive adsorption processes, have been observed in the case of OH and NO 3 uptake by BBA surrogate films (Slade and Knopf, 2013;Knopf et al, 2011), O 3 uptake by benzo [a]pyrene in the presence of water vapor (Pöschl et al, 2001), and O 3 and NO 2 uptake by benzo[a]pyrenecoated soot (Springmann et al, 2009;Kaiser et al, 2011 The presence of higher [O 3 ] may further decrease the OH reactivity of OA (Renbaum and Smith, 2011). Under the applied experimental conditions, the multiphase reaction kinetics involving highly viscous organic material are likely limited by surface-bulk exchange (Arangio et al, 2015;Slade and Knopf, 2014).…”
Section: Oh Generation Flow Conditions and Measurementsupporting
confidence: 53%
“…At RH > 15 %, MNC is less reactive with OH, exhibiting γ < 0.07 due to competitive co-adsorption of water and OH (Slade and Knopf, 2014). Similar suppressions in gas uptake, due to competitive adsorption processes, have been observed in the case of OH and NO 3 uptake by BBA surrogate films (Slade and Knopf, 2013;Knopf et al, 2011), O 3 uptake by benzo [a]pyrene in the presence of water vapor (Pöschl et al, 2001), and O 3 and NO 2 uptake by benzo[a]pyrenecoated soot (Springmann et al, 2009;Kaiser et al, 2011 The presence of higher [O 3 ] may further decrease the OH reactivity of OA (Renbaum and Smith, 2011). Under the applied experimental conditions, the multiphase reaction kinetics involving highly viscous organic material are likely limited by surface-bulk exchange (Arangio et al, 2015;Slade and Knopf, 2014).…”
Section: Oh Generation Flow Conditions and Measurementsupporting
confidence: 53%
“…When exposed to low temperatures, aqueous organic particles can form glasses which are disordered amorphous solids [ Murray , 2008; Zobrist et al , 2008, 2011; Koop et al , 2011]. During transport, aerosol particles can undergo various atmospheric aging processes including, but not limited to: (1) condensation of SOA due to photochemical processing of VOCs [ Seinfeld and Pandis , 1998; Kanakidou et al , 2005], (2) heterogeneous oxidation by atmospheric trace gases such as O 3 , NO 3 , and OH which can lead to the formation of hydrophilic functional groups on the particle surfaces [ Akhter et al , 1985; Smith et al , 1988; Chughtai et al , 1991; Kanakidou et al , 2005; Zuberi et al , 2005; Knopf et al , 2006; Rudich et al , 2007; Daly and Horn , 2009; Springmann et al , 2009; George and Abbatt , 2010; Knopf et al , 2011a; Kaiser et al , 2011], and (3), condensation of hydrophilic material such as inorganic acids, i.e., H 2 SO 4 and HNO 3 [ Jang et al , 2002; Riemer et al , 2004; George and Abbatt , 2010]. Modifications of surface chemistry can affect the particles' hygroscopicities and ice nucleation efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Springmann et al (2009) have demonstrated the applicability and usefulness of the PRA framework Pöschl et al, 2007) for atmospheric modeling of the degradation of benzo[a]pyrene on soot by ozone and nitrogen dioxide. In this study we show that the PRA model approach can be efficiently extended to other PAHs and photo-oxidants.…”
Section: Introductionmentioning
confidence: 99%